Solar drying of peeled longan using a side loading type solar tunnel dryer: Experimental and simulated performance - S. Janjai (2018)
This article presents experimental and simulated results of drying of peeled longan in a side-loading solar tunnel dryer. This new type of solar tunnel dryer consists of a flat-plate solar air heater and a drying unit with a provision for loading and unloading from windows at one side of the dryer. These are connected in series and covered with glass plates. A DC fan driven by a 15-W solar cell module supplies hot air in the drying system. To investigate the experimental performance, five full-scale experimental runs were conducted and 100 kg of peeled longan was dried in each experimental run. The drying air temperature varied from 32 to 76°C. The drying time in the solar tunnel dryer was 16 h to dry peeled longan from an initial moisture content of 84% (w.b.) to a final moisture content of 12% (w.b.), whereas it required 16 h of natural sun drying under similar conditions to reach a moisture content of 40% (w.b.). The quality of solar-dried product was also good in comparison to the high-quality product in markets in terms of color, taste, and flavor. A system of partial differential equations describing heat and moisture transfer during drying of peeled longan in this solar tunnel dryer was developed and this system of nonlinear partial differential equations was solved numerically by the finite difference method. The numerical solution was programmed in Compaq Visual FORTRAN version 6.5. The simulated results agreed well with the experimental data for solar drying. This model can be used to provide the design data and it is essential for optimal design of the dryer.